Effect of caffeinated gum on a battery of rugby-specific tests in trained university-standard male rugby union players - Ranchordas, M. K.; Pratt, H.; Parsons, M.; Parry, A.; Boyd, C.; Lynn, A. (Journal of the International Society of Sports Nutrition, 2019)
Background: Caffeine has been shown to enhance strength, power and endurance, characteristics that underpin performance in rugby. Caffeinated gum has attracted interest as a novel vehicle for delivering caffeine, because absorption of caffeine from gum is quick. Rapid absorption of caffeine may be useful during rugby matches when there is limited time for supplementation such as at half-time or when substitutes enter play. The purpose of this study was to determine whether a low dose of caffeine in gum improves performance in a battery of rugby-specific tests. Methods: In a double-blind, randomized, placebo-controlled, crossover design, 17 male university-standard rugby players (mass: 85.6 ± 6.3 kg; height: 179.4 ± 6.2 cm; age: 20.4 ± 1.2 years) chewed caffeinated gum (200 mg caffeine) or a placebo gum on two occasions separated by a week. After a standardized warm-up, gum was chewed for 5 min. Subsequently, participants performed three countermovement jumps, followed by an Illinois agility test, 6 × 30 m repeated sprints, and the Yo-Yo IR-2 test; each test was separated by short rest periods. Results: Caffeinated gum enhanced countermovement jump by 3.6% (caffeine: 43.7 ± 7.6 cm vs. placebo: 42.2 ± 6.2 cm; d = 0.22, 95% CI [0.006, 0.432]; p = 0.044). There was a greater resistance to fatigue during the 6 × 30 m repeated sprint test (fatigue index caffeine: 102.2 ± 0.9% vs. placebo: 103.3 ± 1.2%; d = 1.03, 95% CI [0.430, 1.613]; p = 0.001), and performance on the Yo-Yo IR2 was improved by 14.5% (caffeine: 426 ± 105 m, placebo: 372 ± 91 m; d = 0.55, 95% CI [0.130, 0.957]; p = 0.010). Caffeine gum had no significant effect on the Illinois agility test (caffeine 16.22 ± 1.08 s vs. placebo 15.88 ± 1.09 s; d = - 0.31, 95% CI [- 0.855, 0.240]; p = 0.271). Conclusions: In university-standard rugby players, a low dose of caffeine (200?mg) supplied in chewing gum enhanced performance on the Yo-Yo IR-2 test and the countermovement jump test and reduced fatigue index during repeated sprints. These improvements in a battery of rugby-specific tests may transfer to enhanced performance in rugby matches.